Lipid profile in hospitalized patients with COVID-19 depending on the outcome of its acute phase: data from the international registry "Dynamics analysis of comorbidities in SARS-CoV-2 infection survivors" - G. P. Arutyunov; E. I. Tarlovskaya; A. G. Arutyunov; Yu. N. Belenkov; A. O. Konradi; Yu. M. Lopatin; A. P. Rebrov; S. N. Tereshchenko; A. I. Chesnikova; G. G. Airapetyan; A. P. Babin; I. G. Bakulin; et al. (Российский кардиологический журнал, 2022)
Aim. To study the lipid profile in hospitalized patients with coronavirus disease 2019 (COVID-19) depending on the outcome of its acute phase according to the AKTIV international registry.Material and methods. The AKTIV registry included men and women over 18 years of age with a diagnosis of COVID-19, who were treated in a hospital. A total of 9364 patients were included in the registry, of which 623 patients were analyzed for levels of total cholesterol, low-density lipoprotein cholesterol (LDL-C) and triglycerides on days 1-2 of hospitalization. The level of high-density lipoprotein cholesterol (HDL-C) was calculated using the Friedewald equation.Results. We found that a decrease in LDL-C level was significantly associated with an unfavorable prognosis for hospitalized patients with COVID-19. This pattern persisted in both univariate and multivariate analyses. LDL-C levels in the final multivariate model had a significant relationship with the prognosis (an increase in the death risk by 1,7 times with a decrease per 1 mmol/l). In addition, we found that the survival of patients with an indicator level of <2,45 mmol/l is significantly worse than in patients with an LDL-C level ≥2,45 mmol/l. All patients with high LDL-C ((≥4,9 mmol/l) survived, while among patients with low LDL-C (<2,45 mmol/l. All patients with high LDL-C ((≥4,9 mmol/l) survived, while among patients with low LDL-C (<1,4 mmol/l), mortality was 13,04%, which was significantly higher than in patients with LDL-C ≥1,4 mmol/l (6,32%, p=0,047).Conclusion. A decrease in LDL-C in the acute period is significantly associated with an unfavorable prognosis for hospitalized patients with COVID-19. Determination of LDL-C can be included in the examination program for patients with COVID-19. However, the predictive value of this parameter requires further study in prospective clinical studies.